Case Study in Outcomes Evaluation : Mongolia - World Bank (Washington, DC, 2014)
From 2010 to 2013, the World Bank governance partnership facility (GPF) and the Swiss Agency for Development and Cooperation (SDC) helped build the capacity of Mongolian civil society organizations (CSOs) to promote good governance and an effective civil society engagement in procurement and service delivery monitoring. An assessment of results from the interventions was needed to satisfy accountability and learning needs and to inform decisions on future programs and funding. However, the short-term, complex nature of the interventions, numerous CSOs involved, and scarce documentation meant that knowledge of results was largely limited to activities and impact will be difficult to measure. In fall 2013, the World Bank and Mongolia office of SDC decided to use an outcome mapping approach to evaluate the effectiveness, sustainability, and relevance of these interventions. Outcome mapping is a participatory methodology useful for evaluating complex programs that involve capacity and coalition building, multiple actors, and tacit knowledge. It looks beyond outputs and delivery efficiency to institutional behavioral changes that occur in and among social actors influenced by interventions. The evaluation provided benefits to the stakeholders in several ways: results were packaged into an accessible, narrative format for various communication purposes; lessons were identified on what worked and did not work to inform the design of future CSO support, particularly concerning social actors and their roles, innovative solutions, and how to adapt or scale up a program; and the participatory process promoted stakeholder learning and ownership of results achieved to date. Thus, the evaluation generated robust, locally validated data that demonstrated the value of the interventions to stakeholders and donors and revealed ways to improve implementation and management for future efforts.